The science of â€œomicsâ€ for plant pathologists - ANANDARAJ*, M. (Indian Phytopathology, 2016)
It was a moment of exhilaration and joy when I heard from the Secretary of the Indian Phytopathological Society that I have been elected unanimously as the president of the society. I was overwhelmed by the warmth and confidence of the members and would ever remain grateful for this kind gesture. The society has grown to this level by the vision, foresight and untiring efforts of pioneer leaders in plant pathology and I recollect their contributions with reverence. During my tenure as president the executive committee and general body were gracious enough to agree for opening a new zone in the Northeast for the benefit of the students from this region. I am sure the society will be growing and contributing not only for the growth of the science of plant pathology but to help and advice policy makers in matters relating to plant disease management and reduction of crop losses to enhance productivity of crop plants. The growing population of India is poised to overtake China in about a decade and half and India will be the most populous country in the world. This is putting the onus on the Indian agricultural scientists to grow more food, feed, fibre and fodder under shrinking natural resources like land, water and non availability of labour. The global warming and climate change could affect the plant diseases and there is increased pressure on the plant pathologists to minimize crop losses.